2013
DOI: 10.4021/jh108e
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association Between ABO Blood Group and Microangiopathic Hemolytic Anemia?

Abstract: Elmer This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Microangiopathic hemolytic anaemia has a strong relation with Non-O blood groups, making them a risk factor for this group of disease. 8 Venous thromboembolism and ischemic stroke are seen in blood groups A and AB. 9 In another study, showed that the von Willebrand factor plays a major role in the clotting mechanism so a higher risk of deep vein thrombosis in individuals belonging to the blood group Non-O is seen due to a higher level of this factor.…”
Section: Discussionmentioning
confidence: 99%
“…Microangiopathic hemolytic anaemia has a strong relation with Non-O blood groups, making them a risk factor for this group of disease. 8 Venous thromboembolism and ischemic stroke are seen in blood groups A and AB. 9 In another study, showed that the von Willebrand factor plays a major role in the clotting mechanism so a higher risk of deep vein thrombosis in individuals belonging to the blood group Non-O is seen due to a higher level of this factor.…”
Section: Discussionmentioning
confidence: 99%
“…Factor VIII activity does not differ significantly between A, B and AB, blood types although it is generally higher in AB blood types. [4][5][6][7][8][9] Several previous studies have demonstrated that factor VIII activity is influenced by age, sex and blood types in healthy people. According to Cooperber & Teitelbaum, factor-VIII is higher in the elderly and in males.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies have claimed that non-O blood types have the risk of thrombosis and O blood type with the risk of hemorrhage. 4,6,8,[10][11][12] Factor-VIII is an acute phase protein and is increased temporarily during an inflammatory process. Kamphuisen's study showed no relationship between factor VIII activity and CRP (C-Reactive Protein) in venous thrombosis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Blood type O is associated with reduced circulating levels of von Willebrand factor, which is a component of the intrinsic clotting pathway [9,10]. Subjects with blood type O are more likely to suffer from coagulopathy such as secondary posttonsillectomy hemorrhage and epistaxis [11,12]. The tendency to bleed associated with blood type O might be proposed to be the reason for Achilles tendon rupture [7,8].…”
Section: Introductionmentioning
confidence: 99%